2008
DOI: 10.1021/ie8006819
|View full text |Cite
|
Sign up to set email alerts
|

Ball Mill-Assisted Dechlorination of Flexible and Rigid Poly(vinyl chloride) in NaOH/EG Solution

Abstract: Both flexible and rigid forms of poly(vinyl chloride) (PVC) were effectively dechlorinated in NaOH/ethylene glycol (EG) solution during ball mill pulverization. The high degree of dechlorination obtained was attributed to the increased surface area of the crushed PVC particles and the resulting enhancement of contact between the PVC and dissolved hydroxide ions. The common additives diisononyl phthalate and CaCO3 were easily separated from the PVC bulk during the dechlorination reaction. The reaction proceeded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 12 publications
1
20
0
1
Order By: Relevance
“…[89] Thep rocess can also be run in wet and basic conditions. [90] As another pre-treatment for pyrolysis,asteamexplosion treatment has been shown to lower the liquefaction temperature by 50 8 8Cf or PS and by 100 8 8Cf or HDPE. [91] 2.1.2.…”
Section: Emerging Technologiesmentioning
confidence: 99%
“…[89] Thep rocess can also be run in wet and basic conditions. [90] As another pre-treatment for pyrolysis,asteamexplosion treatment has been shown to lower the liquefaction temperature by 50 8 8Cf or PS and by 100 8 8Cf or HDPE. [91] 2.1.2.…”
Section: Emerging Technologiesmentioning
confidence: 99%
“…Recently, mechanochemistry has been widely applied in chemical and material synthesis with the unique advantage of enabling efficient solid-state reactions and the ability to directly convert various recalcitrant feedstocks. [61][62][63][64][65][66][67][68][69][70][71][72][73][74] A series of studies transforming biomass in a solvent-free way have been demonstrated. For example, cellulose was converted to watersoluble oligomers by both mineral acids and solid acids in a ball milling process, 75,76 while lignin was decomposed similarly in the presence of a base.…”
Section: Introductionmentioning
confidence: 99%
“…The release of HCl is one of the major problems associated with PVC recycling since the generated vapors are toxic and lead to corrosion of treatment systems. In pyrolysis of PVC, for example, in addition to the generation of HCl, other chlorinated organic molecules can be produced, which make the products undesirable for use as feedstock or fuel [ 2 , 3 ]. The dehydrochlorination begins at thermally labile defect site in the polymer chain.…”
Section: Introductionmentioning
confidence: 99%